Optimizing locked nucleic acid/2'-o-methyl-RNA fluorescence in situ hybridization (LBA/2'OME-FISH) procedures for bacterial detection - Azevedo, Andreia Sofia Mateus (2019)
info:eu-repo/semantics/publishedVersion